Graduate Competencies under the Thai Qualifications Framework for Higher Education in Educational Administration - Ngamkanok, Sumet (Journal of Education Studies, Chulalongkorn University, 2024)
This research aimed to 1) study graduate competencies under the Thai Qualifications Framework for higher education in educational administration; 2) develop indicators for developing graduate competency for higher education in educational administration, 3) create a competency development manual for graduates under the Thai qualifications framework for higher education in educational administration. Research instruments included a semi-structured interview form for collecting data and experts interview conclusions to develop indicators and create the questionnaire for evaluation and focus group. There were three stages of the research procedures: 1) studying competency components of graduates under the Thai Qualifications Framework in educational administration; 2) developing competency indicators for graduates under the Thai Qualifications Framework in educational administration; and 3) creating a manual for developing graduate competency for higher education in educational administration. The results revealed that 1) there were four competency components of graduates under the Thai Qualifications Framework in educational administration (knowledge, skills, ethics, and character); 2) there was a total of eighty indicators for graduates under the Thai Qualifications Framework in educational administration (40 each for master’s degree and doctorate’s degree). The indicators for each degree comprised 10 knowledge indicators, 10 skills indicators, 10 ethnics indicators, and 10-character indicators; and 3) manual evaluation of graduate competency for higher education in educational administration was divided into four aspects: righteousness, appropriateness, possibility, and benefits. The overall evaluation was found to be at the highest level, and each measured item was found to be at the highest level.